Optimalisasi Pelaksanaan Proyek Dengan Critical Path Method Studi Kasus PT. MNC Play Media Medan - Daniel Pakpahan (Journal of Computer System and Informatics (JoSYC), 2019)
The process of optimizing planning to project control during the implementation of development is an important activity of a project, the success and failure of a project can be caused by inefficient planning so that it will cause delays. The critical path method (CPM) method can be used to measure project completion times more efficiently and effectively, so as to reduce the impact of delays and swelling on costs. This can be proposed by the project crashing process with three control alternatives: (i) adding labor, (ii) overtime work, (iii) adding subcontracts. With these results the expected results will be faster than project estimates at PT. MNC PLAY MEDIA MEDAN.